PROFIL PENDERITA CARCINOMA MAMMAE DI RSUP H. ADAM MALIK TAHUN 2019-2020 - Indri Mahrani; Rahmatika Duri (PRIMER (Prima Medical Journal), 2022)
Background : Breast cancer is the most common type of carcinoma  in inpatients and outpatients in all hospitals in Indonesia, with total of 12,014 patients or 28.7% of all types of carcinoma . Objective : To know the profile of breast cancer patients in RSUP H. Adam Malik in 2019-2020 Methods :  Descriptive retrospective. Results : The most experienced maternal age was 41-50 years old is 38 patients (38%), the most BMI experienced are mothers >25, about 51 patients (51%), the highest education experienced mothers are SMA / SMK, namely 56 patients (56%), the most occupations experienced breast cancer are housewives, namely 47 patients (47%), the age at menarche experienced the most breast cancer are <12 years about 66 patients (66%), marital status with mothers are married, namely 91 patients (91%), the history of breastfeeding with the most mothers answer yes, namely 81 patients (81%), the history of contraception experienced the most mothers answers yes, namely 80 patients (80%), a family history with the most mothers having breast cancer, about 52 patients (52%), a family history of other carcinoma are 95 patients (95%). Conclusion : The most age is 41-50 years, BMI is at most >25, education is SMA/SMK, most occupations are housewives, most menarche age is <12 years, most marital status is married, most breastfeeding is breastfeeding, history of most are using contraception, family history with mammary carcinoma.